Seasonal Variation and Significance of Alkaline Phosphatase Activity on Algal Blooming in Chongqing Urban Section of Jialing River - Pu, Peng; Zhang, Zhi; Wang, Min (Asian Journal of Chemistry, 2014)
Water samples were collected in a main branch of upstream Yangtze river, Jialing river, from 5 sampling sites along Chongqing to study the significance of alkaline phosphatase activity to algal blooming in discharging stage of three Gorges reservoir. The seasonal evolution of phosphorus fraction, alkaline phosphatase activity, algal cells amount and enzymatic kinetic parameters were investigated from 2011 to 2012. Results showed the amount of algal cells was highest in discharging stages with low dissolved inorganic phosphorus and was lowest in flood stages with high dissolved inorganic phosphorus. An expected negative correlation (y = 0.0054x-1.6428, R2 = 0.5153) between alkaline phosphatase activity and dissolved inorganic phosphorus and positive correlation (y = 0.0821x+0.3867, R2 = 0.7266) between alkaline phosphatase activity and algal cells amount were found. However a higher ratio of total nitrogen and total phosphorus indicated phosphorus limitation during discharging stage. The co-occurring of high alkaline phosphatase activity and algal blooming can be explained that alkaline phosphatase activity induces dissolved organic phosphorus decomposition and mineralization into dissolved inorganic phosphorus, which is bio-available and supports algal growth when algal blooming occurs. The lower Km values and higher Vmax values during discharging stage indicated high substrate affinity and catalysis efficiency. The study covered a full operating period of three Gorges reservoir, focusing on phosphorus fraction, kinetic parameters and their relationship with algal blooming, provided possible explanations of the mechanism of algal blooming under phosphorus limiting conditions and highlighted the ecological significance of alkaline phosphatase activity.